Worker mutualism in an age of entrepreneurial capitalism. (2nd July 2016) - Cobble, Dorothy Sue
ABSTRACT: In this Keynote Address to the 30th AIRAANZ Conference in Sydney, the author identifies three vital and promising models of worker mutualism. These models show that worker mutualism is thriving, even in an era of entrepreneurial and hyper-individualistic capitalism. Indeed, we are at a moment of recovery and reconfiguration for labour and labour movements globally. The three models of worker mutualism are set within a larger context. The author challenges three mythic narratives: labour decline, working-class conservatism and the association of the rise of new forms of work with rising economic inequality that keep scholars from thinking clearly about worker mutualism and entrepreneurial capitalism.